Isolation and crystallization of patchouly alcohol from patchouly oil - Yuliani Aisyah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Patchouly alcohol is the main component in patchouly oil, and its quantity influences to the quality and price of patchouly oil in trade. According to ISO 3757:2002 standard, the patchouly oil have to contain 27-35% of patchouly alcohol and according to SNI 06-2385-2006 standard, they have to contain at least 31%. Cromatography gas is the standard method recomended by ISO 3757/2002 for testing the quality of patchouly oil. This method requires the original compound of pure patchouly alcohol as the reference material. However the authentic compound of pure patchouly alcohol is not yet available in the chemical trade. Therefore, research should be focused on determining a patchouly oil standar as laboratory reference testing in Indonesia. The experiment of isolation patchouly alcohol from patchouly oil was conducted using fractional distillation method. The isolated patchouly alcohol was identified by gas chromatography-mass spectrometry method. The isolation gave 6.23% yield of patchouly alcohol, and the purity of isolated patchouly alcohol was 95.68%.